Perancangan dan Simulasi Sistem Kendali Kolektor Surya pada Sistem Pembangkit Daya Tenaga Matahari - Sonong Sonong; Apollo Apollo (Politeknik Negeri Ujung Pandang, 2014)
This paper discussed about simulation of closed loop position control system of DC servo motor in solar collector thermal power plant application. When the input position that simulated with step signal given to motor, the positional information from an output potentiometer which is mechanically coupled to a motor is feedback to control amplifier. The references position input from input step is combined with the feedback signal at the input of the amplifier which drivers the motor in proportion to the difference between two signal. In this case, the position of DC servo motor controlled with PID controller. Simulation was created by Simulink toolbox of Matlab 6.50. we found constant PID control are Kp = 1, Ki = 0,4, and Kd = 0,5.